Monitoring Children's Grow And Development Using Preschool Motoric Activity Stimulation Bag (PREMOACTION Bag) - Saraswati, Ni Putu Ayu Melianita (Formosa Journal of Science and Technology, 2024)
The Preschool Motoric Activity Stimulation Bag (Premoaction Bag) represents an innovative educational tool designed to enhance motor development in preschool-aged children. This research aims to investigate the effectiveness of the Premoaction Bag in fostering fine motor skills among children aged 2-6 years. Utilizing a mixed-methods approach, the study evaluates developmental progress in children using the Premoaction Bag compared to a control group. Results indicate significant improvements in motor skills among the experimental group, suggesting that structured and interactive activities are crucial for early childhood development.